Determinants of survival and hospitalization in older, heart failure patients receiving home healthcare. (15th March 2016) - Muñoz, M.A.; Real, J.; Del Val, J.L.; Vinyoles, E.; Mundet, X.; Frigola-Capell, E.; Llauger, M.A.; Orfila, F.; Domingo, M.; Verdú-Rotellar, J.M.
Abstract: Introduction: Since reported evidence is both scarce and controversial, the objective of this study is to determine the risk factors involved in the prognosis of older patients with heart failure (HF) receiving home healthcare from primary care professionals. Methods: Retrospective cohort community study was carried out in 52 primary healthcare centers in Barcelona (Spain). A follow-up was performed between January 2009 and December 2012 with 7461 HF patients aged > 64 years. Information was obtained from primary care electronic medical records containing clinical data, functional and cognitive status, total mortality, and hospital admissions for cardiovascular events. Results: Mortality and hospitalization during follow-up were higher in older, HF patients who received home healthcare than those who did not (HR 1.39, 95% CI 1.22–1.58 and 1.92 95% CI 1.72–2.14, respectively). The most relevant determinants for mortality were male gender (HR 1.40, 95%CI 1.10–1.79), previous hospital admission for HF (HR 1.29 95%CI 1.05–1.60), and severe dependence in activities for daily living (ADL) (HR 1.33, 95%CI 1.06–1.67). In contrast, severely dependent ADL patients were not more frequently hospitalized as a consequence of cardiovascular events (0.97, 95% CI 0.77–1.23). Conclusions: Due to their greater comorbidity and age, mortality and hospitalization in patients requiring home healthcare were higher than those who did not. Among the HF patients receiving home care, mortality and hospital admissions were higher in men, older patients, and in those previously hospitalized for HF. Severe dependence in ADL determined a higher mortality but was not related to increased hospital admission rates.